Martorell's hypertensive ischemic leg ulcer: a case report - Galal El Anany; Noha Nagui; Hanan Nada; Mona Rabeaa; Iman Sany; Ahmad Nada; Ahmed Abo El-Gheit; Omar El Ghanam (Wolters Kluwer Medknow Publications, 2020)
Martorell's hypertensive leg ulcer is a unique form of lower extremity ischemic ulcers that is associated with underlying hypertensive state. In this case report, we present a 61-year-old hypertensive patient with the characteristic ulcer, which was totally cured with treatment, along with a concise review of the condition to renew the appreciation of the existence of this clinical entity.